2007
DOI: 10.1016/j.bbaexp.2007.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The direct p53 target gene, FLJ11259/DRAM, is a member of a novel family of transmembrane proteins

Abstract: The tumor suppressor p53 regulates diverse biological processes primarily via activation of downstream target genes. Even though many p53 target genes have been described, the precise mechanisms of p53 biological actions are uncertain. In previous work we identified by microarray analysis a candidate p53 target gene, FLJ11259/DRAM. In this report we have identified three uncharacterized human proteins with sequence homology to FLJ11259, suggesting that FLJ11259 is a member of a novel family of proteins with si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 17 publications
2
31
0
Order By: Relevance
“…17,18 p53 itself can also induce autophagy in a DRAM (damage-regulated autophagy modulator)-dependent manner in human osteosarcoma saos-2 cell line. 19,20 In accordance with those studies, we hypothesize that proteasomal inhibition can upregulate autophagy in VM neurons and p53 may play a role in this process of induction.…”
Section: Introductionsupporting
confidence: 56%
“…17,18 p53 itself can also induce autophagy in a DRAM (damage-regulated autophagy modulator)-dependent manner in human osteosarcoma saos-2 cell line. 19,20 In accordance with those studies, we hypothesize that proteasomal inhibition can upregulate autophagy in VM neurons and p53 may play a role in this process of induction.…”
Section: Introductionsupporting
confidence: 56%
“…Crighton 21 has identified a p53 target gene DRAM, encoding a lysosomal protein that induces macroautophagy, as an effector of p53-mediated cell death. 41 The present study demonstrated that the p53 specific inhibitor PFT as well as the autophagy specific inhibitor 3-MA effectively blocked the 3-NP-induced induction of DRAM and LC3-II and striatal cell death. These studies suggest that p53 activates autophagy and autophagy activation contributes to 3-NP-induced striatal neuronal death.…”
Section: Discussionmentioning
confidence: 79%
“…In order to avoid massive cell death, observed when Sox2 levels were elevated at least 4-fold above the endogenous level (Mitsui et al, 2003;Kopp et al, 2008;Tonge and Andrews, 2010), we generated cell clones with SOX2 expression driven by cytomegalovirus immediate-early promoter (CMV-IE), which exhibited weak activity in ES and EC cells (Niwa et al, 1991;Liew et al, 2007). The use of CMV-driven constitutive overexpression in NT2/D1 cells has been reported for several genes, such as pluripotency-related fibroblast growth factor-4 (FGF-4) and p27, as well as for FLJ11259/DRAM (Maerz et al, 1998;Baldassarre et al, 2000;Kerley-Hamilton et al, 2007). Using this expression system we obtained 54 resistant colonies.…”
Section: Discussionmentioning
confidence: 99%